Healthcare Resource Utilization and Costs Following Diagnosis of Nontuberculous Mycobacterial Lung Disease in the USA. (4th October 2017) - Marras, Theodore; Mirsaeidi, Mehdi; Chou, Engels; Eagle, Gina; Zhang, Raymond; Wang, Ping; Zhang, Quanwu
Abstract: Background: Despite increasing awareness of nontuberculous mycobacterial lung disease (NTMLD), reports on the economic impact of healthcare resource utilization (HCRU) and costs are limited. Methods: The national managed care insurance database was searched for physician claims for NTMLD (ICD9 031.0 or ICD10 A31.0) on ≥2 separate occasions ≥30 days apart between 2007 and 2016. A patient cohort ( n = 1039) was selected by including those who were insured continuously over 36 months. A control group ( n = 2078) was randomly selected from the plan members without NTMLD and matched 2:1 to the NTMLD sample by age and sex. The diagnosis date of NTMLD patient was assigned to the matched controls as the index date. HCRU and standardized costs were summarized over 12 months (baseline) before NTMLD diagnosis and 2 subsequent years. Results: Mean age was 68 years with 67% women. Charlson comorbidity score was 2.0 (±2.2) in NTMLD vs 0.5 (±1.3) in control. NTMLD patients had substantially more respiratory and other disorders compared with the control group (20.6% vs 3.5% asthma, 36.7% vs 0.3% bronchiectasis, 50% vs 6% ColoradoPD, 2% vs 0% cystic fibrosis, 41.6% vs 1.4% pneumonia, 7.8% vs 0% tuberculosis) and had greater immunosuppressant use (43.8% vs 11.9%). NTMLD vs control group had a 30.5% vs 6.0% rate of hospitalization at baseline, 35.1% vs 6.9% at year 1, and 23% vs 7.3% at year 2. Mean (median) total annual healthcare costs in NTMLD vs control were $35, 145 ($15, 493) vs $5, 660 ($587) at baseline, $47, 248 ($18, 626) vs $6, 692 ($745) at year 1, and $28, 959 ($11, 385) vs $7, 184 ($819) at year 2. Medical costs were $26, 626 ($11, 701) vs $4, 370 ($209) at baseline, $35, 508 ($12, 416) vs $5, 248 (288) at year 1, and $20, 036 ($6, 715) vs $5, 488 ($400) at year 2; pharmacy spending was $8, 519 ($2, 209) vs $1, 290 ($21) at baseline, $11, 739 ($3, 957) vs $1, 444 ($45) at year 1, and $8, 923 ($2, 418) vs $1, 696 ($55) at year 2. Conclusion: Observed HCRU and costs are substantially higher in NTMLD vs control group and increase from baseline to year 1 then decrease to year 2 in NTMLD but continue to rise in control group. The reversed U-shape of total costs in patients with NTMLD may reflect joint economic outcomes of disease, comorbidity, and management. Disclosures: E. Chou, Insmed Incorporated: Employee,  Salary; G. Eagle, Insmed Incorporated: Employee,  Salary; R. Zhang, Insmed Incorporated: Consultant, Consulting fee; P. Wang, Insmed Incorporated: Employee,  Salary; Q. Zhang, Insmed Incorporated: Employee, Salary